2017
DOI: 10.1007/s10864-017-9288-1
|View full text |Cite
|
Sign up to set email alerts
|

Imagine Math Facts Improves Multiplication Fact Fluency in Third-Grade Students

Abstract: Math fact fluency is foundational for later mathematics education. Unfortunately, many students across the nation continue to struggle with these core skills. Computer-assisted instruction may be a potentially valuable tool for improving math fact fluency due to its ability to differentiate instruction at the student level, provide added practice opportunities, and improve student interest and motivation. However, research is currently lacking to demonstrate the effectiveness of many computer-assisted interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The NAP is equivalent to the Mann-Whitney U statistic and ranges from 0 to 1, with 0.50 indicating a null effect of the treatment or a complete overlap between the baseline and intervention phases (Mann and Whitney, 1947;Parker and Vannest, 2009;Michiels et al, 2018). Values above or below 0.50 indicate improvement or regress in performance in the treatment phase in comparison to the baseline, with increasing degrees of non-overlap (Parker et al, 2011;Berrett and Carter, 2018). We calculated nap with an online calculator available at http://www.…”
Section: Non-overlap Of All Pairsmentioning
confidence: 99%
“…The NAP is equivalent to the Mann-Whitney U statistic and ranges from 0 to 1, with 0.50 indicating a null effect of the treatment or a complete overlap between the baseline and intervention phases (Mann and Whitney, 1947;Parker and Vannest, 2009;Michiels et al, 2018). Values above or below 0.50 indicate improvement or regress in performance in the treatment phase in comparison to the baseline, with increasing degrees of non-overlap (Parker et al, 2011;Berrett and Carter, 2018). We calculated nap with an online calculator available at http://www.…”
Section: Non-overlap Of All Pairsmentioning
confidence: 99%
“…Additionally, Rushton et al (2016) stated that the mastery of math fluency has a positive impact on students' sense of efficacy, which can help lead to future math achievement. Several other studies (e.g., Berrett, & Carter, 2018;Kelley, 2008;Ramos-Christian et al, 2008;Poncy & Skinner, 2006) have also found that students who were not proficient in math fact fluency in elementary grades were less likely to succeed in later grades and that this lack of proficiency continued to be a significant barrier to pursuing advanced mathematics in middle and high school.…”
Section: Students With Ld and Math Fact Fluencymentioning
confidence: 93%